Knud Jeppesens Kontrapunkt – og de andres: Nogle observationer vedrørende kildegrundlaget for et udvalg af lærebøger i vokalkontrapunkt fra det 20. århundrede - Holme Hansen, Thomas (Danish Yearbook of Musicology, 2001)
Knud Jeppesen’s Kontrapunkt (Vokalpolyfoni), first published in 1930, became the most influential textbook on sixteenth-century counterpoint in the 20th century. In this book, which was translated into several languages and widely disseminated, Jeppesen provided a unique pedagogical tool based on the species-counterpoint which has proven its worth to the present day. During the preceding decades an increasingly number of manuals and textbooks on sixteenth-century counterpoint have been published, most of them acknowledging Jeppesen’s importance, none of them actually claiming to replace his book. Limiting itself to some preliminary and general observations on a selection of these textbooks the article focuses on the sources on which the textbooks are based and in this respect comments on some obvious methodological problems. Finally, the textbooks are evaluated in the light of the actual research published during the second half of the 20th century.